Geriatric nutritional risk index predicts perioperative cardiovascular events in older patients with coronary artery disease undergoing non-cardiac surgery: a multicenter retrospective cohort study - Li, Xiaolin; Wang, Congying; Jiang, Haodong; Zhu, Jia; Wu, Runzhe; Niu, Yongquan; Chen, Feiyu; Jin, Yunpeng (Frontiers in Nutrition, 2025)
BackgroundThe relationship between geriatric nutritional risk index (GNRI) and perioperative cardiovascular events (PCE) remains underexplored. This study aimed to evaluate the predictive utility of GNRI for PCEs in older patients with coronary artery disease (CAD) undergoing non-cardiac surgery.MethodsThis multicenter retrospective study analyzed consecutive patients aged ≥ 65 years with documented CAD undergoing non-cardiac surgery between 2013 and 2024 at two Chinese tertiary medical centers. The primary outcome was a composite of PCEs, including death, resuscitated cardiac arrest, myocardial infarction, heart failure, and stroke, occurring intraoperatively or during postoperative hospitalization.ResultsAmong 7,272 participants, 408 (5.6%) experienced PCEs. GNRI exhibited a significant inverse linear correlation with PCEs (OR = 0.92; 95% CI: 0.91–0.93; p < 0.001). Using a GNRI cutoff of 98, the at-risk group (GNRI < 98) had a significantly higher incidence of PCEs compared to the no-risk group (GNRI ≥ 98) (univariate OR = 4.840; 95% CI: 3.947–5.935; p < 0.001; multivariate OR = 1.919; 95% CI: 1.496–2.461; p < 0.001). GNRI demonstrated comparable discriminatory ability to revised cardiac risk index (RCRI) (C-statistics: 0.676 vs. 0.694, p = 0.309). A weighted scoring system incorporating GNRI and RCRI significantly outperformed either index alone in predicting PCEs (vs. RCRI: C-statistics 0.768 vs. 0.694, p < 0.001; vs. GNRI: C-statistics 0.768 vs. 0.676, p < 0.001).ConclusionThe GNRI independently predicted PCEs in older CAD patients undergoing non-cardiac surgery. Integrating GNRI into clinical decision-making may enhance perioperative risk stratification and management in this high-risk population, though further validation is warranted.